The Potential Impact of COVID-19 on Tuberculosis: Recent Trends and Future Approaches to TB Management - Iqbal, Muhammad Naeem; Iqbal, Iqra; Ashraf, Asfa (PSM Microbiology, 2022)
Coronavirus disease 2019 (COVID-19) has captured the attention of healthcare practitioners and academics since it was declared a worldwide pandemic. Other epidemic communicable diseases, such as tuberculosis (TB), are still a public health concern that may grow and drain healthcare infrastructure. There is growing evidence on the biological, clinical, and epidemiological interaction between tuberculosis and COVID-19 disease. The COVID-19 pandemic has upended TB control efforts and has impacted resource provision for TB diagnosis, treatment, and prevention. In this review, we focus on the impact of COVID-19 on tuberculosis and summarize the current developments in the management of TB and the perspectives for future developments. New approaches are necessary in order to reduce TB incidence and mortality. There is need to design extremely effective medication regimens that can achieve high cure rates independent of the resistance patterns of strains.